Clorox Inc : was the company's jump into 'green' personal care a smart move or a strategic misstep? - Rindfleisch, Elise, (SAGE knowledge. Cases., 2016)
In October 2007, Clorox announced that it would buy Burt's Bees for $925 million - more than five times Burt's Bees' annual sales. Clorox's move caught many in the industry by surprise. The company was known for bleach, auto polish and other synthetic chemical cleaners. On the other hand, the much smaller Burt's Bees was best known for its trademark natural lip balm. Could such a brand find a home within the company?